US-China economic relations and impact on the world economy. Case study of Apple Inc. - Alkenov, Dayan (2023)
The trade war between China and the United States creates problems in the supply chain and unforeseen risks for companies. Many corporations are forced to change their business strategies and relocate their manufacturing facilities. Apple was forced to relocate their main suppliers and find ways to deal with governments of China and the US. Research question is: How Apple Inc. was impacted by the trade war? As a result we can see that Apple was using its power over supplies to force them to move to countries of SouthEast Asia (India, Thailand, Vietnam), and was lucky to have TSMC moving its facilities to the US.